Percepção da qualidade pelos clientes em uma empresa de fast food: um estudo sobre a rede Giraffas de Araguaína - TO. - Santos, Sergio Gomes dos (Universidade Federal do Tocantins, 2020)
The relevance of this research is associated with increased food consumption outside the home, in view of the expectation of customers require quality in the services provided. With the changes presented by the market, organizations seek strategies that maintain the quality of its services, because they need to keep up with changes inconsumer behavior and develop new strategies for competitiveness. This scientific work introduces the concept of emergence of Fast Food, quality, and service, and the relationship between service and client satisfaction, since the same is returned to customer perception. This article aims to demonstrate and measure the quality under the perception of customer satisfaction in the services of quick power Araguaína-TO.Like all scientific research must follow a methodological guideline, this investigationtook the following steps: the work begins with a theoretical review concepts, therefore the methodology are presented, and the conclusion. Despite being aware of the importance of satisfaction of expectations of the client and the quality of the service, there are still differences between what the client expects, and the service provided at the company.